Pengembangan Media Pembelajaran Apeme Cupang untuk Membuktikan Rumus Volume Kerucut - Agus Miftakus Surur; Nabila Elsa Gunawan; Adisa Eka Damayanti; Delisya Awal Fitriana; Vina Pramudya U.; Muhammad Khoiril Akhyar (Jurnal Ilmiah Pendidikan Matematika Al Qalasadi, 2023)
Apeme Cupang media is a media used to prove the volume of a cone is equal to 1/3 the volume of a tube. The purpose of making this media is to overcome the limitations of the senses in the complicated process of proving the volume of the cone. In addition, the purpose of making this apeme cupang media is to attract students' attention in learning the volume of tubes and cones. Researchers used an R&D approach with the ADDIE model. The activity begins with first analyzing the needs, which shows that students still have difficulty in cone material about proving the cone formula, so a proof media is designed. The second stage begins to make designs and prepare the tools and materials needed. The third stage begins the development process that is adjusted to the design that has been made. In this stage, it explains the process of making apeme cupang media made from cardboard paper until the media is ready for use. After that, conduct a review to media experts and material experts to show the validity of the media. The results of the review obtained some input which was then revised. Once sufficient, the media can be tested on students. This trial stage uses an individual trial which in the end obtained input from students that shows the practicality of the media. As a further step, the media is valid and can be applied in the classroom which is also the fourth stage, namely implementation, and closed with the evaluation stage.